ANALISIS PERILAKU KEUANGAN PADA PELAKU USAHA KECIL SALON KECANTIKAN DI KOTA ENDE - Tanusi, Gabriel (ANALISIS, 2024)
Beauty salon service business management is influenced by financial behavior,including financial knowladge, financial experience, and educational level. Problems faced managing finances include : do not yet have reguler financial records, there is no seperation of company and personal finance, have not planed savings, investments, the average level of formal education is high school, and has not taken business financial management training.This research aims to determine and analyze the partial influence of financial knowledge,financial experience and education level on the financial behavior of beauty salon service business actors in the city of Ende. This type of research is quantitative research with a population of 30 people. Date collection techniques used questionnaires and interviews.The date analysis tecnique uses multiple linier regression analysis. The research show that there is a positive and significant influence of financial knowledge on the financial behavior of beauty salon service business in Ende City, there is a positive and significant influence of financial experienceon on the financial behavior of beauty salon service business in Ende City, there is a positive and significant influence of the level of education on the financial behavior of beauty salon service business in Ende City.